2020
DOI: 10.26434/chemrxiv.12523136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Fungal Metabolites Bergenin, Quercitrin and Dihydroartemisinin as Potential Inhibitors Against Main Protease of SARS-CoV-2

Abstract: Emergence of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection has given rise to COVID-19 pandemic, that is wreaking havoc worldwide. Therefore, there is an urgent need to find out novel drugs to combat SARS-CoV-2 infection. In this backdrop, the present study was aimed to assess potent bioactive compounds from different fungi as potential inhibitors of SARS-CoV-2 main protease (M<sup>pro</sup>) using an <i>in-silico</i> analysis. Nearly 118 bioactive compounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…8 ) was found to inhibit 11.9% of the SARS-CoV-2 M pro at 50 µM and could be a lead molecule for the development of more potent inhibitors, while taking into account the anti-inflammatory as well as the adverse health risks of this drug.
Figure 8 Molecules most recently reported to demonstrate potential in silico SARS-CoV-2 M pro inhibitory activity 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 .
…”
Section: Sars-cov-2 Main Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 ) was found to inhibit 11.9% of the SARS-CoV-2 M pro at 50 µM and could be a lead molecule for the development of more potent inhibitors, while taking into account the anti-inflammatory as well as the adverse health risks of this drug.
Figure 8 Molecules most recently reported to demonstrate potential in silico SARS-CoV-2 M pro inhibitory activity 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 .
…”
Section: Sars-cov-2 Main Protease Inhibitorsmentioning
confidence: 99%
“…Using molecular docking and MD simulations, Kumar et al [75] reported the compounds withanone and caffeic acid phenethyl ester to be better inhibitors of SARS-CoV-2 than withaferin-A, and they were as equipotent as the covalent protease inhibitor N3. Patel et al [76] showed that fungal metabolites such as bergenin and dihydroartemisinin were slightly better inhibitors than N3 when virtually screened against the SARS-CoV-2 M pro , but not better than the flavonoid glycoside quercitrin. Lyndem et al [77] screened naturally occurring coumarin derivatives and identified corymbocoumarin, methylgalbanate and heraclenol as potential SARS-CoV-2 M pro inhibitors, but they were less potent than control drugs such as lopinavir or ritonavir.…”
Section: Sars-cov-2 Main Protease Inhibitorsmentioning
confidence: 99%
“…44 Fonsecin, a naphthopyrone pigment from Aspergillus fonsecaeus mutant has shown high binding affinity for SARS-COV-2 PLpro by interacting with the Tyr 268 amino acid residue of enzyme cavity based on in silico molecular docking and molecular dynamic studies. 43,45 The genome of Penicillium thymicola contains a polyketide synthase and a nonribosomal peptide synthetase hybrid gene cluster, which upon expression leads to the synthesis of Pyranonigrin A. Pyranonigrin A. is a secondary fungus metabolite with strong inhibitory capability against the SARS-CoV-2 Mpro. 43,46…”
Section: Studies On Potentials Of Endophytes Against Coronavirusmentioning
confidence: 99%
“…Furthermore, in adjustment Cox proportional hazard models, patients neither receive combination of drug nor alone one, there were no significant difference in mortality [5]. Nature has always overwhelmed us with many new and unique bioactive compounds which possess potent activity against various disease and infection [6]. Hence, there is prerequisite of scientific community to draw the diverse knowledge of traditional system [7].…”
Section: Introductionmentioning
confidence: 99%